Liver metastasis biology and clinical management - Brodt, Pnina (Springer, 2011)
Liver metastases are a frequent and often fatal occurrence in cancer patients, particularly those with malignancies of the gastrointestinal (GI) tract. While recent improvements in surgical techniques and a more aggressive approach to resection of liver metastases have improved long term survival for some patients, most patients with hepatic metastases still succumb to their disease. To improve these dismal statistics, a better understanding of the biology of liver metastasis, particularly the early stages that can be targeted for prevention, is essential.  Once cancer cells enter the liver, several different scenarios may occur. The cancer cells may be immediately destroyed by local defence mechanisms, they may enter a state of dormancy as solitary cells and never produce a metastasis, initiate a short-lived process of proliferation that is aborted before a metastasis is established or actively proliferate to form macrometastases. The chapters in Part I of this book provide insight into the cellular/molecular mechanisms that determine which of these scenarios prevails.  Written by experts researchers in the filed of metastasis, these chapters provide state-of-the art reviews on the cellular and molecular processes that impact the early stages of the metastatic process. The unique microenvironment of the liver, its various anatomical, cellular and molecular features and the impact they have on metastasis are highlighted. In addition, the role of inflammation (pre-existing and tumor-induced), host innate and adaptive immune responses, cytokines, chemokines, growth factors and the unique molecular signatures of metastatic tumor cells are reviewed with an underscoring of the translational implications of the current state of knowledge.  Against this background, the chapters in Part II of the book provide critical reviews on major aspects of the clinical management of hepatic metastases. These include imaging strategies, surgical and chemotherapeutic treatment approaches and the use of targeted biological therapeutics such as anti-angiogenic drugs as treatment modalities.   By combining information on biological and clinical aspects of liver metastasis, this volume  will serve as an excellent resource for scientists, clinicians, clinician/ scientists and trainees in the domains of oncology, surgical oncology, hepatobiliary physiology and radiology.